PENERAPAN TEKNOLOGI BIOGAS DAN KOMPOS ELA SAGU DALAM UPAYA PENINGKATAN KESEJAHTERAAN PETERNAK SAPI DI DESA MAMALA KABUPATEN MALUKU TENGAH - Ch W Patty; L Joris; I Sangadji (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2020)
These days energy has become one of the most important needs for society, considering the scarcity of basic household needs such as kerosene and firewood. The fulfilling of these needs could be solved by utilizing renewable energy. Some renewable energy only needs simple technology to be produced, such as biogas. Biogas could be produced through utilizing the farm waste such as cow manure that are generally wasted and polluted the environment.In Mamala Village, Central Maluku, the technology to produce biogas could be developed, considering the status of mamala as one of the center for cow husbandry in Central Maluku. Currently there are around 79 that are farmed by either group of farmers or individual farmers. The needs for compost in this village are very high because of the rarity and the expensive price of chemical fertilizers (inorganic), meanwhile 51,74% of the resident of this village are grow corps as their main source of income. The usage of chemical fertilizer also decreases farms production. Therefore, the supply of organic fertilizer such as compost that could be produced with cow manures, and sagoo waste should be increased. The produced composts could be sold or used for any kind of crops that are being cultivated in the village to feed livestock. In return the vegetables that are cultivated to feed livestock could also be sold to increase prosperity of the villagers.